Gideon Mendel - freedom or death - Mendel, Gideon 1959- (GOST, 2019)
Thirty years ago, photographer Gideon Mendel left a box of negatives and transparencies in storage in a friend's garage in Johannesburg. At some point the box was rained upon and the top layers damaged. The affected photographs were from Mendel's documentation of the final years of apartheid when he had witnessed the nationwide township uprising and scenes of mobilization, conflict and tragedy. This act of happenstance led to Mendel revisiting and re-engaging with his archives, and the gradual creation of this book Freedom or Death.
Keywords: Mendel, Gideon -- 1959-; Brodsky, Marcelo -- 1954-; Fotografie; Apartheid; Südafrika; Documentary photography / South Africa; Altered prints; Anti-apartheid movements / South Africa / Pictorial works; South Africa / History / 1961-1994 / Pictorial works; Mendel, Gideon; Anti-apartheid movements; Documentary photography; South Africa; 1961-1994; History; Pictorial works; Bildband